2020
DOI: 10.1017/s1041610220001489
|View full text |Cite
|
Sign up to set email alerts
|

Time to diagnosis in younger-onset dementia and the impact of a specialist diagnostic service

Abstract: Objectives: While early diagnosis of younger-onset dementia (YOD) is crucial in terms of accessing appropriate services and future planning, diagnostic delays are common. This study aims to identify predictors of delay to diagnosis in a large sample of people with YOD and to investigate the impact of a specialist YOD service on this time to diagnosis. Design: A retrospective cross-sectional study. Setting: The inpatient unit of a tertiary neuropsychiatry service in metr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 24 publications
5
87
3
Order By: Relevance
“…Limited research has specifically explored the predictors of time to care home admission, yet not focused on SES and was limited by its small sample of people with AD and Lewy Body dementia; 29 Yaffe et al, 2002 18 . The timeliness of the initial dementia diagnosis can be a limitation in the present study, as it is well known that there are severe delays in getting a diagnosis in the first place 30 . This means that some people might receive a diagnosis whilst already being in the more advanced stages of the condition, whilst others might have received a diagnosis more quickly, which will inevitably have an implication on the time to care home placement.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Limited research has specifically explored the predictors of time to care home admission, yet not focused on SES and was limited by its small sample of people with AD and Lewy Body dementia; 29 Yaffe et al, 2002 18 . The timeliness of the initial dementia diagnosis can be a limitation in the present study, as it is well known that there are severe delays in getting a diagnosis in the first place 30 . This means that some people might receive a diagnosis whilst already being in the more advanced stages of the condition, whilst others might have received a diagnosis more quickly, which will inevitably have an implication on the time to care home placement.…”
Section: Discussionmentioning
confidence: 92%
“…-515 dementia diagnosis can be a limitation in the present study, as it is well known that there are severe delays in getting a diagnosis in the first place. 30 This means that some people might receive a diagnosis whilst already being in the more advanced stages of the condition, whilst others might have received a diagnosis more quickly, which will inevitably have an implication on the time to care home placement. Unfortunately, no data were available on first symptom recognition, as this data linkage used routinely collected data.…”
Section: Discussionmentioning
confidence: 99%
“…Our work demonstrated that a multidisciplinary specialist YOD clinic within a tertiary hospital decreases the time to diagnosis (Loi et al, 2020). We propose the implementation of a 'hub-and-spoke' model (Elrod and Fortenberry, 2017) in which at least one specialist YOD clinic is available in each state/territory.…”
Section: Action 1: Promote Pathways To Care For Timely Diagnosismentioning
confidence: 92%
“…Alzheimer's disease, frontotemporal dementia) and a range of neurological disorders and substance and injuryrelated disabilities. An average 4.7year delay in diagnosis occurs partly because early symptoms can differ from the typical late-life presentation (Loi et al, 2020). People with YOD and their families face significant distress and burden owing to their familial, professional and financial responsibilities at the time of symptom onset (Cations et al, 2017).…”
mentioning
confidence: 99%
“…Previous work in the area has highlighted the various challenges related to YOD. These include the heterogeneous nature of symptom presentation which can lead to diagnostic delay (Draper et al, 2016;Loi et al, 2020b;van Vliet et al, 2013), difficulties with access to appropriate service provision for both the patient and their families (Sansoni et al, 2016;Cations et al, 2017), and the associated distress and psychiatric effects on both of these parties (van Vliet et al, 2011). In addition, authors have suggested diagnostic instability in YOD, particularly in people who present with psychiatric symptoms (Woolley et al, 2011;Perry et al, 2019).…”
Section: Introductionmentioning
confidence: 99%